Which Model for Poverty Predictions? - Paolo Verme (Global Labor Organization (GLO), 2020)
OLS models are the predominant choice for poverty predictions in a variety of contexts such as proxy-means tests, poverty mapping or cross-survey impu- tations. This paper compares the performance of econometric and machine learning models in predicting poverty using alternative objective functions and stochastic dominance analysis based on coverage curves. It finds that the choice of an optimal model largely depends on the distribution of incomes and the poverty line. Comparing the performance of different econometric and machine learning models is therefore an important step in the process of opti- mizing poverty predictions and targeting ratios.
Keywords: D31; D63; E64; O15; 330; Welfare Modelling; Income Distributions; Poverty Predictions; Imputations